Molecular detection of food-borne Aeromonas species - Ghatak, S; Agarwal, R K; Bhilegaonkar, K N; Gill, J P S (The Indian Journal of Animal Sciences, 2012)
The members of the genus Aeromonas have emerged as an important food-borne pathogen that pose many challenges to the scientific community. Difficulties regarding aeromonads involve its debated taxonomy, true role as pathogen and detection, particularly from foods. Various conventional techniques involving culture media and broths have been devised for identification form foods and immunological techniques viz. ELISA protocols have been standardized. Due to shortcomings of these methodologies molecular techniques were explored. These included nucleic acid hybridization probes, various formats of PCR, restriction fragment length polymorphism, amplified fragment length polymorphism, pulsed field gel electrophoresis, real time PCR, sequence analysis, DNA microarray technique, etc. Many of these modern assays have been promising, indicating that future detection paradigm for detection of Aeromonas will predominantly be based on molecular techniques. In this communication we have attempted to review these available molecular tools for detection of aeromonads from foods.